(untitled) (Heritage, 2022)
The author often mentioned in his works that there is no state, no inhabited territory on the globe that is immune to terrorism. Although the roots of terrorism go back a long way, its causes and motives are different. Therefore, the author identifies terrorism as a world problem, which is never isolated in one environment, but very quickly, like a forest fire, spreads to other areas. In the era of rapid information and technological development, the concept of terrorism is becoming less and less clear, even though it is used more. Given that we have seen in the not-so-distant past that terrorist organizations are unscrupulous in their attacks, one of the main concerns of modern times is undoubtedly the possibility of using biological weapons for terrorist purposes. This paper analyzes in detail the somewhat intimidating form of terrorism, known as bioterrorism, a distinction was made between this and other types of terrorism, and we have given a historical view of the use of biological weapons, all with the aim of more precisely defining this extremely complex phenomenon.